Criminal Law Reform In Criminal Responsibility For People In Mental Disorders Oriented To Dignified Justice - Tedjokusumo, Dave David; Siswanto, Carissa Amanda (Universitas Semarang, 2023)
This article aims to analyze the nature of criminal responsibility and criminal law reform in ODGJ criminal responsibility which is oriented towards the theory of dignified justice. The urgency of this study is that the application of the formulation of offenses in the provisions of Article 44 of the WvS Criminal Code is not appropriate for perpetrators of criminal acts who are malingering, lack of legal protection to victims. Therefore, a reform of criminal law is needed. In the preparation of this research using normative juridical legal research methods carried out through literature review as the basic material for analysis. The result of the discussion of this study is that the reform of criminal law, especially in ODGJ criminal liability which has been regulated in Article 38 juncto Article 39 of the National Criminal Code, where the rule of law is more appropriate, and has been oriented towards the theory of dignified justice. In addition, it is also necessary to pay attention to the role of relevant law enforcement officials such as the Police and Hospitals which in this case issue Visum et Repertum (VeR), because correct law enforcement is also needed from law enforcement officials.